(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Current research on lead (Pb) in relation to the thyroid and particularly thyroid cancer remains limited. Objective: To compare Pb concentrations in blood and thyroid tissue samples between the patient and control groups; evaluate the association between Pb concentrations and thyroid cancer. Methods: A cross-sectional descriptive study was conducted on 282 patients with benign and malignant thyroid tumors at stages 1, 2, and 4. Lead concentrations in blood and thyroid tissue were measured, and their correlation with thyroid cancer was analyzed. Results: The blood Pb concentration in the patient group was 1.27 ± 2.33 µg/L, while in the control group, it was 0.65 ± 2.35 µg/L. The Pb concentration in thyroid tissue for the benign and malignant groups was 15.26 ± 72.87 µg/kg and 36.88 ± 74.32 µg/kg, respectively. Logistic regression analysis showed that blood Pb levels in the malignant thyroid tumor group were higher than in the benign group (OR = 1.270; 95% CI: 1.011–1.594; p = 0.040). High Pb concentrations in thyroid tissue were associated with thyroid cancer (OR = 1.006; 95% CI: 1.000–1.011; p = 0.043). Conclusion: High Pb concentrations in thyroid tissue and blood samples are associated with thyroid cancer.